The difference of blood pressure before and after consuming Green Kiwi (Actinidia deliciosa) in the young adult group - Lesmana, Dian; Rizali, Ervin; Kintawati, Silvi (Faculty of Dentistry Universitas Padjadjaran, 2013)
Introduction: Green Kiwi fruit (Actinidia deliciosa) has a lot of nutritional content, one of them is potassium. Potassium helps maintain osmotic pressure in intracellular fluid, protect body’s electrolyte balance, regulate heartbeat, maintain muscle and nerve cell function, reduce the risk of stroke and heart disesase, and decrease blood pressure. Methods: This study is an experimental research, using pair t-test measurement to analize the difference of blood pressure before and after consuming Green Kiwi fruit (Actinidia deliciosa) in early adulthod. The sample are thirty five students of Faculty of Dentistry, Padjadjaran. The number of green kiwi fruit is consume as much as 1 fruits or 150 grams. Blood pressure measured by sphygmomanometer with auscultatory-palpation method. Results: The result of this study shows the averaged blood pressure before and after consuming green kiwi fruit Is 99,543/68,438 mmHg and 97,581/66,743mmHg. Conclusion: The conclusion of the study indicates the existence of difference in blood pressure before and after consuming Green Kiwi fruit (Actinidia deliciosa) in early adulthood (p<5%).